Оценка местных сортообразцов граната в условиях Апшеронского полуострова - Мустафаева, З.П. (Фактори експериментальної еволюції організмів, 2015)
Aims. Systematize genetic resources grenade Punica granatum L. (Punicaceae) by studying and comprehensive assessment of newly received material in the Absheron peninsula. Methods. Each class and promising form of given production and biological characteristics based on the methodology «Descriptors on the grenade» Massoud Mars (Spain, 1977), which is held on a range of important functions by comparing plants under identical conditions. Results. The article presents the results of the evaluation of local accessions of pomegranate «Shirin Girmizi», «Donuz Burnu», «Ulvi» and «Velez from Qazyan››, introduced from other regions (Agdash, Goychay), but grown and bear fruit in terms of the Apsheron. Conclusions. The studies revealed that the studied accessions may be suitable for cultivation in the Absheron peninsula Keywords: Punika granatum L., genetic resourses, estimation.